Linking Character Strengths and Key Competencies in Education and the Arts: A Systematic Review - Pedro Vazquez-Marin; Francisco Cuadrado; Isabel Lopez-Cobo (MDPI AG, 2022)
Positive education, as a method for the positive development of students' personality, embodies the 24 character strengths that Peterson and Seligman developed in their studies and that are necessary for new professional profiles. This new social and work landscape inspired supranational institutions, such as the European Union, to develop theories for new educational systems. These Key Competencies seek the comprehensive training of students, on not only the cognitive but the socioemotional plane, as occurs with arts education. With this literature review, we intend to demonstrate the relationship between the Key Competencies as catalysts for the development of character strengths in students through art education programmes. The results conclude that it is possible to define a relationship between the Key Competencies and character strengths and to outline the nature of these relationships, noting that certain patterns of combinations of strengths are repeated in the Key Competencies. Additionally, our work leads us to propose the need to increase the volume of research in this field and to design future studies that allow an empirical evaluation of the nature of these connections and whether they are efficient and enduring.